Association of GH and IGF-1 polymorphisms with growth traits in a synthetic beef cattle breed - Pereira, Andréa Pozzi; Alencar, Maurício Mello de; Oliveira, Henrique Nunes de [UNESP]; Regitano, Luciana Correia de Almeida (Sociedade Brasileira de Genética, 2005)
The Canchim beef cattle (5/8 Charolais + 3/8 Zebu) has been selected for meat production in Brazil since late 1950. In the present work the effects of growth hormone (GH) and insulin-like growth factor 1 (IGF-1) polymorphisms were investigated in 688 animals born between 1998 and 2000. These animals belonged to two genetic groups, i.e., traditional and new lineages. Genotype effects on expected breeding values for birth weight (BW), weaning weight (WW) and yearling weight (YW) were investigated by the least square method. Significant effects were found for GH genotype on YW (p < 0.05), with positive effects associated with the LV (leucine/valine) genotype. For IGF-1 genotypes, significant effects were found on BW (p < 0.01) and YW (p < 0.01). Average substitution effects for IGF-1 alleles estimated by regression analysis suggested a positive effect of the IGF-1 225 bp allele on BW and of the 229 bp allele on YW.
Keywords: Beef cattle; Genetic association; Genotype; growth hormone; insulin-like growth factor 1